Man and Nature. A New Project on New Spirituality - Pasek, Zbigniew; Dyczewska, Agnieszka (Problemy Ekorozwoju, 2012)
This article is a prelude to a planned project aimed at researching new ways of understanding and redefining the concept of nature in the so-called New Spirituality movements. The authors begin from a theoretical context associated with the meaning, for religious studies, of the sacred – profane and culture – nature dichotomies, and show the changes religiousness undergoes. Today we see an increasing number of people turning away from traditional forms of religious cult with a simultaneously declared wish to develop their own spirituality. New spirituality is provisionally defined here as the worldly transgression of the human condition committed in the name of different values​​ strongly associated with the physical (bodily) dimension of life and a holistic vision of the world. On the basis of examples, drawn mainly from publications based on the Deep Ecology trend, the authors discuss three aspects: (1) a new understanding of one’s own nature, (2) a new understanding of the nature of the world; and (3) new forms of activity for changes in awareness. In the dimensions under discussion, the process of recently locating the element of the sacred in the profane sphere and the resacralisation of nature clearly emerges. In the conclusions we also consider to what extent the formative new spirituality on the ecological trait can help to popularise the ​sustainable development idea within the framework of changing the religiousness of man at the start of the twenty-first century.